Kelompok Pemuda Gerakan Masyarakat Sehat di Kota Palu, Sulawesi Tengah - Amsal, Amsal; Junaidi, Junaidi; Cahyani, Yayuk Eka; Hafid, Fahmi (Pusat Penelitian & Pengabdian Masyarakat Poltekkes Kemenkes Palu, 2023)
The Healthy Community Movement (GERMAS) efforts are preventive and control measures for Non-Communicable Diseases, especially among adolescents. The shift in disease patterns (epidemiological transition) during the productive age significantly influences future health status. Diseases that can strike during the productive age include stroke, Coronary Heart Disease (CHD), cancer, and diabetes, which rank highest among illnesses. The objective of this Community Service activity is to enhance awareness, willingness, and the ability of the community to adopt clean and healthy lifestyles through GERMAS, targeting adolescents aged >15 years. Community Service activities were conducted in the Mamboro Barat Sub-district of North Palu, Palu City. The activities included stretching exercises, communal fruit consumption, educational sessions using informative and interactive leaflets, lectures, weight measurement, height measurement, waist circumference measurement, blood pressure measurement, cholesterol examination, blood sugar examination, and uric acid examination. The results obtained showed that out of 26 participants, 9 individuals had a waist circumference >90, 19.2% were classified as hypertensive, 42.3% had high cholesterol, 23.1% were classified as having diabetes mellitus, and 53.8% were categorized as having high uric acid. Implementing the healthy community movement in adolescents in the Mamboro Sub-district requires attention, especially in promoting a healthy lifestyle by maintaining dietary patterns, consuming vegetables and fruits, and adopting healthy behaviors.